2017
DOI: 10.1038/s41467-017-01112-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of influenza A virus NP acetylation on viral growth and replication

Abstract: Lysine acetylation is a post-translational modification known to regulate protein functions. Here we identify several acetylation sites of the influenza A virus nucleoprotein (NP), including the lysine residues K77, K113 and K229. Viral growth of mutant virus encoding K229R, mimicking a non-acetylated NP lysine residue, is severely impaired compared to wildtype or the mutant viruses encoding K77R or K113R. This attenuation is not the result of decreased polymerase activity, altered protein expression or disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…Acetylation enhances the enzymatic activity of the HIV integrase and increases its affinity for DNA (Cereseto et al, 2005). More recently, it was shown that acetylation of highly conserved lysine residues might regulate specific functions of nucleoprotein in the viral life cycle of influenza A viruses, including viral replication (Giese et al, 2017). Lastly, we have found that the mechanisms by which human fragments and duplications increase the net load differ.…”
Section: Discussionmentioning
confidence: 88%
“…Acetylation enhances the enzymatic activity of the HIV integrase and increases its affinity for DNA (Cereseto et al, 2005). More recently, it was shown that acetylation of highly conserved lysine residues might regulate specific functions of nucleoprotein in the viral life cycle of influenza A viruses, including viral replication (Giese et al, 2017). Lastly, we have found that the mechanisms by which human fragments and duplications increase the net load differ.…”
Section: Discussionmentioning
confidence: 88%
“…Acetylation is an important post-translational modification in eukaryotes, but the occurrence and function of acetylation in influenza viral proteins remain largely unclear. Giese et al reported that acetylation of 77 K, 113 K, and 229 K of NP proteins is important for virus polymerase activity and replication [27]. In the present study, we identified and characterized the acetylation of K108 in the NS1 protein, and the deacetylation of K108Q affected viral replication in cells at 36 and 48 hpi.…”
Section: Discussionmentioning
confidence: 52%
“…Acetylation has been found in multiple proteins of influenza viruses. Acetylation was identified in the NP protein of influenza virus, and deacetylation of the NP protein prevented the virus from assembling functional virus particles [27]. A histone-like sequence (histone mimic) was identified in the NS1 protein of influenza A H3N2, which contributes to suppression of the antiviral response [28].…”
Section: Introductionmentioning
confidence: 99%
“…As a major component of the vRNP complex, NP mediates the nuclear import and export of the vRNP complex in the virus life cycle, and the function of NP is affected by various modifications and host factors (36,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). Previous studies identified several amino acids in NP that are involved in the NP posttranslational modifications of ubiquitination, phosphorylation, sumoylation, and acetylation, thereby affecting viral replication or virulence in vitro or in vivo (51, 52, 54, 55).…”
Section: Discussionmentioning
confidence: 99%